Foraging for the Optimal Dressing Scaffold to Carry Adipose-Derived Stromal/Progenitor Cells for Cell Therapy - Chia-Chieh Wu; Ying-Che Chen; Yi-Chia Wu; Shu-Hung Huang; Yur-Ren Kuo; Su-Shin Lee (Cell Transplantation, 2022)
In our daily plastic surgery practice, we have seen many chronic wounds that need new biotechnology to help and improve wound healing. Stem cells play a crucial role in regenerative medicine. Many pre-clinical researches had reported the beneficial paracrine effects of stem cell therapy for chronic wounds. Cell-friendly scaffolds may provide the protection and three-dimensional space required for adherence of stem cells, thus allowing these stem cells to proliferate and differentiate for treatment purpose. A successful scaffold may enhance the effects of stem cell therapy. In this presented series, the authors attempted to identify the most suitable scaffolds from several commercially available wound dressings that could sustain adipose-derived stromal/progenitor cells (ADSCs) survival. Therefore, we isolated ADSCs containing the green fluorescent protein (GFP) from GFP transgenic rats. The GFP (+) ADSCs and their progenies could be easily observed using a fluorescence microscope. Moreover, we analyzed the cytokines secreted in condition medium (CM) to understand the activities of ADSCs in various dressings. Our results showed that the foam dressings, hydrofiber, chitosan, and alginate plus carboxymethylcellulose were identified as the most suitable dressing materials. Higher concentrations of transforming growth factor beta (TGF-β) and vascular endothelial growth factor (VEGF) were observed 48 h after loading them with GFP (+) ADSCs. Therefore, multiple topical cell therapy using ADSCs can be performed by applying suitable dressing scaffolds without repeated needle injections to deliver the stem cells into the wound bed. Based on their fluorescence property, the GFP (+) ADSCs can also possibly be used for testing biocompatibility of medical materials in the future.